Agricultural productivity in the COMESA, EAC and IGAD: status, trends and drivers - Karugia, Joseph T.; Massawe, Stella; Guthiga, Paul; Ogada, Maurice; Wambua, Jonesmus (International Food Policy Research Institute, 2011)
The Comprehensive Africa Agriculture Development Programme (CAADP) is a framework that provides for an agriculture-led development strategy. CAADP aims to help African countries alleviate poverty and achieve food security by attaining an average annual agricultural growth rate of 6% through allocating at least 10% of their total annual budgets to the sector. Low agricultural productivity is one of the major challenges facing the agriculture sector on the continent. Agricultural productivity in Africa is significantly lower than in other parts of the world. To achieve the goals and aspirations of CAADP, agricultural productivity must be raised significantly. Generally, productivity is low but information on productivity performance in the Common Market for Eastern and Southern Africa (COMESA) region and other sub-regional groupings in Eastern and Central Africa is not synthesized and compiled for decision making. This report is one of the annual monitoring and evaluation (M&E) reports for CAADP generated by the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) network. It focuses on agricultural productivity with the overall aim of reviewing and comparing trends in agricultural productivity to shed light on the progress being made in addressing agricultural productivity constraints. The report covers COMESA, the East African Community (EAC), and the Intergovernmental Authority for Development (IGAD) and the Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA) member countries. The information provided can help identify possible policy actions and options to address the low agricultural productivity